Micro Finance in Manipur - S, Robita (Ushus Journal of Business Management, 2017)
Manipur lives in villages. The rural population contributes to about 76.12% of the total population. Enhancement in the quality of life of the economically weaker section of the society has been one of the basic objectives of development planning of the State. Rural development, by empowering the rural masses through economic self-reliance, is one of the priority areas of the Central and State Govts. To bring about development in rural areas, the govts. and banks/financial institutions have formulated various programmes and schemes. Micro Finance is one such scheme adopted for the development of rural people.